Ceramic Membranes: Materials – Components – Potential Applications. Issue 6 (26th November 2019) - Meulenberg, Wilhelm A.; Schulze‐Küppers, Falk; Deibert, Wendelin; Gestel, Tim Van; Baumann, Stefan
Abstract: Gas separation in dense ceramic membranes is driven by the partial pressure gradient across the membrane. The mixed conducting materials most commonly used are single‐phase perovskites or fluorites. In recent years, the development of dual‐phase systems combining a mixed ion‐conducting and electron‐conducting phase has increased. The advantage is that a larger number of very stable materials systems is available. The membrane designs currently used include planar, tubular, hollow‐fiber, and honeycomb membranes. Each of these designs has specific advantages and disadvantages, depending on the application. Innovative joining concepts are also often needed due to the high temperatures involved. These usually involve the use of glass‐ceramic sealants or reactive metal brazes. Applications focus either on the separation of gases alone, i.e., the supply of oxygen or hydrogen, or on membrane reactors. In membrane reactors, a chemical reaction occurs on one or both sides of the membrane in addition to gas separation. The supply of gases is of potential interest for power plants, for the cement, steel, and glass industries, for the medical sector, and for mobile applications. Membrane reactors can be used to produce base chemicals or synthetic fuels. Abstract : Ceramic membranes can be used for gas separation and conversion of chemical reactions at high temperatures. In addition to increased efficiency, novel industrial processes are also possible. The properties, production and applications of different membrane materials are described in this article.